Republic of Lithuania : Financial Sector Assessment Program Update-Technical Note-Basel Core Principles of Effective Banking Supervision Assessment. (IMF Staff Country Reports; Country Report ;, 2008)
This Technical Note presents a targeted review and a follow-up on the implementation of the recommendations of the 2002 assessment of Lithuania's compliance with the Basel Core Principles for Effective Banking Supervision. It was found that banking supervision arrangements in Lithuania were of a high standard and either fully or largely complied with the Core Principles. On one Core Principle, Lithuania was judged to be noncompliant at that time, which concerned the lack of explicit legal protection for Bank of Lithuania board members and supervisory staff.